(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research is trying to identify the investment portfolio risks of the insurance company and their impact, on the Profitability ratios of the company, and whether the company’s scientific methods followed in the measurement of these risks, and conducted research in the National Insurance Company. by relying on its annual budget as well as the annual reports, The search dealing with these data in theoretical and practical major premise to statistically significant between to investment portfolio risk and financial performance correlation and reach a set of conclusions and recommendations which are the following. investments include many risks (such as risks of falling stocks and bonds, and the risk of borrowers repay, the risk of currency exchange rates, the risk of fluctuations in the prices of real estate investments, change in interest rates). The main important recommendations of this research are: 1_The need for the insurance company’s commitment to the principle of diversification in its investments because it leads to improved earnings to the company، as well as reduce the investment risk and also provide high liquidity throughout the year, which is one of the important things for the insurance company to be able to fulfill the obligations. 2_The need to focus on short term investments in order to maintain the insurance company’s liquidity and easily converted into cash in order to meet its obligations toward publicly insured, and that the money intended for investment in insurance companies generally consist of two components premiums and capital, Money and its distributed depends on the company’s investment policy by finding a rational investment policy.